2014
DOI: 10.4028/www.scientific.net/ddf.348.261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Structural Integrity of the Jet Pumps of a Boiling Water Reactor under Hydrodynamic Loading

Abstract: The structural integrity of a jet pump assembly of a boiling water reactor (BWR) under hydrodynamic loading was evaluated. This arrangement, which has a riser joined with a couple of jet pumps by the transition piece, is part of the reactor recirculation system. It is submerged in water under pressure. The main function is to induce forced flow through the core of the reactor. A dynamic structural analysis was carried out with the finite element method. The first ten modes of vibration and their natural freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Code and some other procedures [1,5,7,15,16] proposed for the evaluation of the structural integrity of the piping system can be followed. Therefore, a criterion to prevent potential failures of the steam dryer can be established.…”
Section: Discussionmentioning
confidence: 99%
“…Code and some other procedures [1,5,7,15,16] proposed for the evaluation of the structural integrity of the piping system can be followed. Therefore, a criterion to prevent potential failures of the steam dryer can be established.…”
Section: Discussionmentioning
confidence: 99%
“…Natural Frequencies (Hz) Stevens and coworkers [15] Cuahquentzi and coworkers [16] This It was observed that the fourth mode shape is torsional (Figure 6). Its natural frequency is 41.82 Hz.…”
Section: Mode Shapementioning
confidence: 97%
“…Cuahquentzi and coworkers [16] determined the first 10 mode shapes and their natural frequencies with ANSYS code and SAP 2000 code. They considered the hydraulic loads inside the jet pump.…”
Section: Natural Frequencies Of the Jet Pump Assembly Submerged In Watermentioning
confidence: 99%
“…e natural frequencies were evaluated with different gaps at the slip joint. Cuahquentzi et al [16] determined the natural frequencies and the modes of vibration of the jet pumps with a 3D model. Cuamatzi-Meléndez and Flores-Cuamatzi [17] analyzed the response of the natural frequencies versus the displacement, velocity, and acceleration of the structure.…”
Section: Natural Frequencies Of the Jet Pump Assembly Submerged In Watermentioning
confidence: 99%